Empowering Senior High School Teachers: Integration of Lesson Study-Based Inquiry Learning to Build a Learning Community - Kurniasih, Surti; Herawati, Desti; Munarti, Munarti; Herawati, Atti (Universitas Muhammadiyah Malang, 2026)
Inquiry learning is important in the implementation of the independent curriculum, because the Independent Curriculum demands learning that is more based on students' experiences, which actively involves them in the process of seeking knowledge. This community service activity aims to empower teachers at SMAN 1 Ciomas, Bogor Regency through the implementation of lesson study-based inquiry learning as an effort to build a collaborative and sustainable learning community. The implementation method of this activity includes socialization activities of lesson study for learning community (LSLC) and the implementation of 2 cycles of lesson study carried out collaboratively between LPTK and schools involving lecturers, principals, teachers, and prospective teacher students. Lesson study activities in each cycle consist of three stages, namely the Plan, Do, and See stages. The instruments used in this activity include teacher knowledge test instruments related to LSLC and student observation sheet instruments. The results of this community service activity show that teacher knowledge of LSLC increased with an increase in N-Gain of 0.59 (moderate category), the formation of an effective teacher learning community, and an increase in student learning activities. The implementation of lesson study allows teachers to share experiences, ideas, and constructive feedback that will improve the overall quality of learning. With the formation of a teacher learning community at SMAN 1 Ciomas, teachers can be more confident in implementing innovative and effective learning methods in the classroom.